Enhancing Environmental Security in Residential Environments with Technology-Based Security Systems - Ferdiansyah, Muhammad; Dwiono, Sugeng; Olga, Lidia; Nurraihan, Faiq; Andriasari, Sevi (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
The objective of community service is to augment the level of environmental security in residential areas by implementing security solutions that are technology-driven. This approach utilizes advanced technology, such as motion sensors, surveillance cameras, and integrated security systems, to monitor and protect residential areas. This methodology is expected to mitigate the possibility of unlawful behavior and other unforeseen occurrences, while concurrently cultivating a sense of safety among residents. The assessment of the efficacy and efficiency of this technology-driven security system is also carried out through community engagement, which entails the analysis of security incident data both before and after its implementation. The expected results of this study have the potential to make a substantial academic contribution by improving the safety of residential environments and offering vital insights for designing and implementing similar security systems in various housing contexts.